A rigorous examination of electromyography forearm muscle response in grasping and swinging scenarios - Mohd Bukhari Wan Daud, Wan; Osman Tokhi, Mohammad; Sudirman, Rubita; Juzaila Abd Latif, Mohd; Abas, Norafizah; Sutikno, Tole (Bulletin of Electrical Engineering and Informatics, 2025)
This study examines the use of electromyography (EMG) in analyzing forearm muscle responses in hand grasping force with swinging motions. We start by establishing the basics of hand grasping force and swinging motions, laying the groundwork for subsequent discussions. The paper critically assesses various EMG techniques, highlighting how they reveal muscle activity during hand grasping in dynamic situations. We explore how swinging motions affect hand grasping force biomechanics, emphasizing the role of EMG in capturing dynamic muscle activity. A thorough examination of methodologies used in EMG studies provides insights into current practices and emerging trends. Practical applications across fields like rehabilitation and robotics underscore the relevance of this research. The study concludes by addressing current challenges and suggesting future research directions. This synthesis provides a straightforward resource for researchers, practitioners, and technologists seeking a deeper understanding of EMG indices in hand-grasping force analysis with swinging action.